Characteristics of Surface Wave on the Unstable Interface in Gas Jet Forming - Weijie Fu; Xu Zhang; Mingwei Wang; Xinming Zhang (Machines, 2023)
The surface accuracy and quality of the mirror blank determine the performance of the optical mirror after coating; therefore, it is crucial to seek a simple and effective method for mirror blank processing. The gas jet forming provides a new idea, which employs a gas jet to impinge on a liquid pool, forms a specific curved surface and solidifies it. However, due to the interface instability that occurred with a specific range of jet velocity, periodical fluctuations appear on the interface and affect the forming of the mirror blank. In this study, the amplitude and transfer period of surface waves in the air gas/dimethyl silicone oil system are taken as the research objects. After conducting orthogonal experiments, this study uses a high-speed camera to record the generation of the surface wave and the fluctuation of the gas–liquid interface during its transfer. Subsequently, this study analyses the influences of jet velocity and viscosity of dimethyl silicone oil on the amplitude and transfer period of the surface wave. In the following experiments, multiple groups of parameters were selected in the range of jet velocity of 11~13 m/s and dimethyl silicone oil viscosity of 500~2000 Pa·s. This study measures the interface morphology with different parameters using the method of image recognition. Finally, using the measured data, this study establishes the calculation model of surface wave amplitude and transfer period, realizing the study of the characteristics of surface waves on the unstable interface. This research can be used to enhance the forming accuracy of the gas jet-forming method.